2006
DOI: 10.1128/mcb.00405-06
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Chromatin Modifications at a Multigene Locus Generate Asymmetric Transcriptional Interactions

Abstract: Random assortment within mammalian genomes juxtaposes genes with distinct expression profiles. This organization, along with the prevalence of long-range regulatory controls, generates a potential for aberrant transcriptional interactions. The human CD79b/GH locus contains six tightly linked genes with three mutually exclusive tissue specificities and interdigitated control elements. One consequence of this compact organization is that the pituitary cell-specific transcriptional events that activate hGH-N also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…A human bacterial artificial chromosome (BAC) genomic clone encompassing the hGH LCR and the entire hGH cluster was identified by a screen of a total genomic library (CITB Human B&C Library; Invitrogen Life Technologies) with probes corresponding to the TCAM1 and SCN4A genes (69). A 148.3-kb clone (clone 535D15) was identified, and a 123-kb insert was released by NotI digestion.…”
Section: Methodsmentioning
confidence: 99%
“…A human bacterial artificial chromosome (BAC) genomic clone encompassing the hGH LCR and the entire hGH cluster was identified by a screen of a total genomic library (CITB Human B&C Library; Invitrogen Life Technologies) with probes corresponding to the TCAM1 and SCN4A genes (69). A 148.3-kb clone (clone 535D15) was identified, and a 123-kb insert was released by NotI digestion.…”
Section: Methodsmentioning
confidence: 99%
“…Some promoters have an almost complete set of elements to fully activate the gene (Kamat et al, 1999;Klüppel et al, 1991;Rao et al, 2003;Reddi et al, 2007;Yoo et al, 2006), but others have little activity (Grosveld et al, 1987;Heckert et al, 2000;Jones et al, 1995). Therefore, it is very important to evaluate the promoter activity of each gene, and we analyzed the in vivo activity of the POP promoter for the first time by using transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that some promoters had sufficient activity to drive the appropriate gene expression in transgenic mice. For example, promoters of the Pem/Rhox5 gene (Rao et al, 2003), the CYP19 aromatase gene (Kamat et al, 1999), the tyrosinase gene (Klüppel et al, 1991), and the human Ig gene (Yoo et al, 2006) reproduced the tissue-specific expression patterns of the corresponding genes in transgenic mice. Several testis-specific promoters have also been reported to be sufficient for the appropriate gene activation in transgenic mice (Reddi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these early studies, it was concluded that this promoter region, along with its linked enhancer/repressor elements, constituted the core determinants of hCD79b transcriptional control (12). However, subsequent in vivo analyses of hCD79b gene expression using transgenic mouse models have brought into question whether these elements have essential roles in the expression of the hCD79b locus in its native genome environment (13).…”
mentioning
confidence: 99%
“…This complex locus contains multiple DNase I HSs with distinct tissue and developmental specificities (13,(27)(28)(29). The HSs in this region that form in pituitary somatotropes, placental syncytiotrophoblasts, skin fibroblasts, and B lymphocytes have been extensively explored and identified by the combined analyses of chromatin from corresponding cell lines, primary human tissues, and human loci carried in defined transgenic mouse lines (13). These patterns of HSs point to a complex, tissue-specific set of cis-acting elements that are alternatively used to drive mutually exclusive patterns of gene expression in these distinct tissues.…”
mentioning
confidence: 99%